Effects of olanzapine on anhedonia in schizophrenia: mediated by complement factor H - Zhang, Yi; Tang, Wei; Wang, Weiping; Xu, Feikang; Lu, Weihong; Zhang, Chen (Frontiers in Psychiatry, 2023)
Background: Anhedonia is a trans-diagnostic symptom in schizophrenia and MDD. Our recent work indicated that increased plasma level of complement factor H (CFH) is associated with anhedonia in major depressive disorder. This study hypothesized that CFH is likely to be a biomarker of anhedonia in schizophrenia. Methods: A 12-week prospective study is performed to observe the effects of olanzapine on anhedonia and CFH. We used the Chinese version of Snaith-Hamilton Pleasure Scale (SHAPS) to evaluate anhedonic phenotype in patients with schizophrenia. Plasma levels of C-reactive protein (CRP), C3, C4 and CFH were measured. Results: Of the recruited 152 samples, patients with anhedonia were found in 99/152 (65.13%). Patients with anhedonia had notably higher PANSS negative subscores, SHAPS total score and higher level of plasma CFH than those without anhedonia (Ps＜0.05). Stepwise multivariate linear regression analysis showed that increasing level of plasma CFH was a risk factor for SHAPS total score (β=0.18, P=0.03). Of the 99 patients with anhedonia, 74 completed the 12-week follow-up. We observed significantly reduced scores of PANSS, SHAPS and decreased plasma CFH level, when the patients completed this study. The change of SHAPS total score is positively correlated with the level of CFH decrease (P=0.02). Conclusion: Our results implied that plasma CFH levels may be a biomarker for anhedonia in schizophrenia, and the effect of olanzapine on treating anhedonia is through decreasing plasma CFH levels.